Role of Fine Needle Aspiration in The Diagnosis of Metaplastic Carcinoma of Breast - Jinkala, Sreerekha; Neelaiah, Siddaraju; Badhe, Bhawana A (Annals of Pathology and Laboratory Medicine, 2018)
Metaplastic carcinomas of breast are rare primary malignant tumors of breast with high rate of recurrences and metastasis. It poses diagnostic difficulties in histopathology as well as in cytopathology because of its varied morphological features. We present a case of a 54 year old woman diagnosed as metaplastic carcinoma of breast by fine needle aspiration and subsequently by histopathology. Our case shows predominantly mesenchymal components like spindle shaped cells, chondroid matrix material and numerous osteoclastic giant cells along with a scanty malignant epithelial component, which was better appreciated on the FNA material , by which a definitive diagnosis of metaplastic carcinoma of breast was possible on FNA. The epithelial component was underrepresented in the subsequent trucut biopsy, thus emphasizing the adjuvant role of FNA in diagnosing these tumors. In this report we discuss the challenges involved in diagnosing metaplastic carcinoma of breast on FNA.